The effect of physical exercise on circulating brain‐derived neurotrophic factor in healthy subjects: A meta‐analysis of randomized controlled trials - Ya‐Hai Wang; Huan‐Huan Zhou; Qiang Luo; Sidong Cui (Brain and Behavior, 2022)
Abstract Objective To investigate how physical exercise (PE) would affect brain‐derived neurotrophic factor (BDNF) in randomized controlled trials (RCTs) of healthy subjects. Methods Seven databases (PubMed, Web of Science, Cochrane, Embase, PsycINFO, CINAHL, SPORTDiscus) were searched for RCTs assessing the effects of PE on serum and/or plasma BDNF until December 18, 2021. Meta‐analysis was performed by random‐effects method with standardized mean difference (SMD) and 95% confidence intervals (CIs). Subgroup analysis and meta‐regression analysis were conducted to investigate the potential source of heterogeneity. Trim and fill method, and leave‐one‐out cross‐validation were conducted. Results Eventually, 21 articles, involving 809 participants, were included in the meta‐analysis. Overall, both acute (5 trials, SMD: 1.20, 95% CI: 0.36 to 2.04, p = .005) and long‐term (17 trials, SMD: 0.68, 95% CI: 0.27 to 1.08, p = .001) PE had significant positive effects on BDNF levels. Via subgroup analysis, studies of long‐term PE with larger sample sizes, female participants, participants older than 60 years, and aerobic exercise contributed to a more pronounced improvement on BDNF levels than that found when all studies were combined. Conclusion Both acute and long‐term PE had significant positive effects on circulating BDNF in healthy subjects. This review suggests that acute exercise and long‐term aerobic exercise are powerful forms of PE to enhance neurotrophic effect, especially for female subjects or subjects over 60 years.